(untitled) (SCIENCE TIME JOURNAL, 2026)
Diabetes mellitus is one of the most widespread chronic metabolic diseases affecting millions of people worldwide. Effective management of this condition requires not only pharmacological treatment but also appropriate lifestyle modifications, including regular physical activity. This article explores the impact of physical exercise on the health of patients with diabetes mellitus through an analysis of scientific literature. Particular attention is given to the effects of aerobic and resistance exercises on blood glucose regulation, insulin sensitivity, body weight control, cardiovascular health, and overall quality of life. The reviewed studies indicate that regular physical activity improves glycemic control, reduces insulin resistance, and decreases the risk of diabetes-related complications. Exercise also contributes to better cardiovascular function, enhanced physical fitness, and improved psychological well-being. Furthermore, physically active individuals demonstrate greater adherence to treatment recommendations and healthier lifestyle behaviors. The findings confirm that physical exercise is a safe, effective, and essential component of comprehensive diabetes management and should be integrated into routine care programs for diabetic patients.